Are retirees more satisfied? - Anticipation and adaptation effects of retirement on subjective well-being: A panel analysis for Germany - Joachim Merz (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Quality of life and satisfaction with life are of particular importance for individuals as well as for society concerning the "demographic change" with now longer retirement periods. This study will contribute to the life satisfaction discussion and quantifies life satisfaction and pattern of explanation before and after such a prominent life cycle event, the entrance into retirement. In particular, with the individual longitudinal data and 33 waves of the Socio-Economic Panel (SOEP) and the appropriate microeconometric causal fixed effects robust panel methods we ask and quantify if actual life satisfaction indeed is decreasing before retirement, is increasing at the entrance into retirement, and is decreasing then after certain periods back to a fore-going level. Thus, we ask if such an anticipation and adaptation pattern - as known from other prominent events - is also to discover for life satisfaction before and after retirement in Germany. Main result: Individual and family situation lift life satisfaction after retirement for many years, the (former) occupational situation, however, absorbs this effect both for pensioners and civil service pensioners. It remains only one period of improvement with close anticipation and adaptation at entering retirement but no furthermore significant change compared to pre-retirement life satisfaction. This holds for pensioners (German pension insurance, GRV) but there is no significant effect at all for civil service pensioners. – – Lebensqualität und Lebenszufriedenheit ist für den Einzelnen wie aber auch für die Gesellschaft insgesamt vor dem Hintergrund des demographischen Wandels mit nun länger andauernder Phase nach dem Eintritt in den Ruhestand von besonderer Bedeutung. Die vorliegende Studie will zur Diskussion der Lebenszufriedenheit einen empirisch fundierten Beitrag leisten insbesondere die Lebenszufriedenheit vor und nach einem markanten Ereignis, dem Renteneintritt, quantifizieren und dafür Erklärungsmuster finden. Vor allem wird mit den individuellen Verlaufsdaten und 33 Wellen des Sozio-ökonomischen Panels (SOEP) und der mikroökonometrischen kausalen fixed effects robusten Panelanalyse analysiert, ob die individuelle Lebenszufriedenheit tatsächlich vor dem Renteneintritt absinkt, der Renteneintritt sie hochschnellen lässt und sie nach einer gewissen Zeit wieder auf das vorherige Niveau der Lebenszufriedenheit absinkt. Zu klären wird also zu sein, ob sich ein solches Muster herausschält und wie bedeutend Antizipation und Adaption - bekannt von anderen markanten Ereignissen - für die Lebenszufriedenheit vor und nach dem Renteneintritt in Deutschland sind. Hauptergebnis: Individuelle und familiäre Faktoren erhöhen die Lebenszufriedenheit nach dem Renteneintritt für viele Jahre. Allerdings absorbiert die (vormalige) Arbeitssituation diesen Effekt sowohl für GRV Rentner als auch für Pensionäre (Beamte). Es verbleibt nur eine Periode der Verbesserung mit Antizipation und Adaption nahe dem Renteneintritt aber keine signifikante längere Änderung im Vergleich zur Lebenszufriedenheit vor dem Renteneintritt. Dies gilt für GRV Rentner, für Pensionäre wird kein signifikanter Effekt überhaupt feststellbar.
Keywords: I31; J26; J14; J17; A13; C23; 330; retirement; life-satisfaction; happiness; anticipation and adaptation effects; fixed-effect regression; Socio-Economic Panel (SOEP); Renteneintritt; Lebenszufriedenheit; Antizipations- und Adaptionseffekte; Fixed-Effects-Regression; Sozio-oekonomisches Panel (SOEP); Deutschland; Germany